On the heterogeneity and classification of author self-citations - Lawani, S.M. (1982)
The heterogeneity of author self‐citations is highlighted and a systematic scheme for their classification is presented. Self‐citations are either synchronous or diachronous and each of these classes or genera has four subclasses or species. The distribution of self‐citations among the four species is governed by a number of factors including collaborative tendencies in the discipline or research specialty and the relative statuses of the collaborating authors. The classification of self‐citations may be applied to study aspects of research collaboration and the matter of egotism in scholarly work.